(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
An opinion article is one of the text genres that is found easily in mass media. However, in the realm of Indonesian instruction, this type of article is classified as difficult for students to produce. The literature study and interview results with four teachers show the difficulty of applying assessments in terms of text structure. This study examined how to capture the unity of argument in Indonesian opinion articles using Toulmin’s argument model as an analytical tool. Toulmin’s argument contains a Claim-Data-Warrant-Backing-Qualifier-Rebuttal (C-D-W-B-Q-R) pattern. The pattern is applied to analyze an opinion article, it will capture the unity of the author’s arguments that accommodate a particular direction (positive, negative, or neutral). Understanding the application of Toulmin’s argument patterns in an opinion article can help Indonesian teachers in writing instruction, especially writing argumentative text genres. In this study, the researchers emphasized Toulmin’s argument patterns, especially in the assessment component of discourse content.